2023
DOI: 10.1094/pdis-10-21-2291-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Green Mold Disease Caused by Penicillium citrinum on Dictyophora rubrovolvata in China

Abstract: Dictyophora rubrovolvata is a saprophytic mushroom widely cultivated in China, including Guizhou Province for its high nutritional, medicinal, and economical values (Chen et al. 2021). In May 2021, green mold disease was observed on the fruiting bodies of D. rubrovolvata, causing its death or preventing it from forming a sporocarp, in an indoor-production facility at Asuo village, Baiyun District Guiyang city, Guizhou Province, China (26°73'51" N, 106°72'88" E). The disease incidence was 60%-70% in the affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There are many species of pathogenic in edible fungal diseases, such as Agaricus bisporus disease, mainly Pseudomonas tolaasii and Lecanicillium fungicola [47,48]. Some studies have shown that the pathogens in P. rubrovolvatus are Saccharomycopsis phalluae, Penicillium citrinum and T. koningiopsis [3,13,49]. This work enriches the species of pathogens of P. rubrovolvatus.…”
Section: Discussionmentioning
confidence: 76%
“…There are many species of pathogenic in edible fungal diseases, such as Agaricus bisporus disease, mainly Pseudomonas tolaasii and Lecanicillium fungicola [47,48]. Some studies have shown that the pathogens in P. rubrovolvatus are Saccharomycopsis phalluae, Penicillium citrinum and T. koningiopsis [3,13,49]. This work enriches the species of pathogens of P. rubrovolvatus.…”
Section: Discussionmentioning
confidence: 76%